AN ANALYSIS OF USING WHATSAPP TO ENHANCE STUDENTS’ LEARNING OF ADVANCED LISTENING CLASS - Fatma Yuniarti (Politeknik Negeri Bengkalis, 2020)
Education system has developed rapidly, technology has invaded our life, everyone has smart phone these days, using WhatsApp, Facebook, Twitter, Instagram, Telegram, etc. No one can deny that the generation we teach these days, has become addicted to these applications, for social relationship and fun. This study was conducted in English Departmen especially Advanced Listening class. The population of the study were 32 female and 4 male students from 4st level who were studying English Program. The researcher has used the analytical descriptive method to conduct this study in University of Muhammadiyah Pringsewu. A studentsâ€™ questionnaire and instructor observation were the tools for collecting the data, results were coded manually and analyzed using SPSS. Almost all study-findings supported using WhatsApp to enhance students learning and enthusiasm, using WhatsApp helped students to develop English skills, enriched their listening and learn from their mistakes, although the study laid out some disadvantages of the experience such as preparing the materials and having discipline class.Â Keywords: WhatsApp, enhance, experience, language, learning